Bolesław III Wrymouth, the hero of Piarist dramas - Mieszek, Małgorzata (Melusine. Old Literature and Culture, 2024)
The subject of the article is nine printed theatrical summaries (from the years 1682–1723) from Piarist schools in the former Polish-Lithuanian Commonwealth, featuring Bolesław III Wrymouth as the protagonist. The analyzed dramas were part of the educational program of the Piarists, in which the teaching of history held a signiﬁcant place, and Bolesław III Wrymouth himself was presented as an exemplary ﬁgure. The monarch embodied the Piarist educational ideal of a knight making eﬀorts to defend the homeland. He was portrayed as a warrior, knight, sage, politician, and defender of the Christian faith. The article also traces how individual playwrights utilized the same historical events (such as Bolesław’s struggles with the Pomeranians, Moravians, Przecław, the defeat of Yaropolk II of Kiev). It illustrates the serving function of these episodes in relation to the overarching didactic-moralizing idea of the Piarist school stage. The article also addresses the adaptation of historical material to the panegyric character of the presentations.